Short Communication: Sulphur Levels and Fuel Quality in Peninsular Malaysia - M. RAMALINGAM; A. AHMAD FUAD (ASEAN Journal on Science and Technology for Development, 2015)
This paper presents the investigation on sulphur levels in fuels collected from different petrol stations in Peninsular Malaysia. Diesel and gasoline samples were analysed for sulphur using X-ray fluorescence spectrometry technique. In general, diesel concentrations of sulphur were only slightly lower than the Deprtment of Environment’s current sulphur limit of 500 p.p.m. across 2010–2014 (the range was 289–698 p.p.m., 374–410 p.p.m., 319–436 p.p.m., 447–605 p.p.m. and 300–477 p.p.m. for 2010, 2011, 2012, 2013 and 2014, respectively). Sulphur concentrations were relatively low in gasoline samples: the mean figures were 95, 77, 96, 74, 240 and 125 for 2009, 2010, 2011, 2012, 2013 and 2014, respectively when compared with the sulphur limit of 500  p.p.m.. The importance of determining sulphur concentration in fuel oils was critical in the efforts to determine if the vehicles used quality fuels that comply with Euro 2 Standards; and also was relevant in meeting Euro 4 Standards requirement of 50 p.p.m. sulphur that was proposed to be adopted in the future.